Impact of Capital Structure on Financial Performance of Construction and Real Estate Quoted Companies in Nigeria - A., Rufus, Ozioma; N., Ofoegbu, Grace (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper examines the impact of capital structure on the financial performance of quoted Constructionand Real Estate Companies in Nigeria from 2005-2014.The study made use of ex post facto researchdesign which involved gathering panel dataset from the published annual financial statements of firms inthe Construction and Real Estate Sector listed on the Nigerian stock Exchange from 2005 through 2014.Pooled ordinary least square regression was used to analyse the data to identify the relationship between adependent variable and one or more independent variables. The findings of the research revealed thatCapital Structure of showed a positive and significant effect on financial performance proxies by EarningsPer Share, Return on Capital Employed, Return on Equity but its impact on Return on Assets isinsignificant. The result of our study portrays that capital structure of the Construction and Real EstateSector firms listed on the Nigerian stock Exchange has a significant impact on firms’ financialperformance based on the following performance proxies (Earnings per Share, Return on CapitalEmployed, Return on Equity) but does not significantly influence return on assets. It also providesadditional study evidence on capital structure and performance of Nigerian construction and real estatesector.